Difficult Decisions in the Surgical Care of Military Casualties with Major Torso Trauma. Issue Volume 157:Issue (2011)Supplement 3 (1st September 2011) - Bowley, DM; Jansen, JO; Nott, D; Sapsford, W; Streets, CG; Tai, Nigel
Abstract : Testing and difficult decision-making is a sine qua non of surgical practice on military operations. Better pre-hospital care protocols, reduced evacuation timelines and increased scrutiny of outcome have rightfully emphasised the requirement of surgeons to "get it right, first time and every time" when treating patients. This article addresses five contentious areas concerning severe torso trauma, with relevant literature summarised by a subject matter expert, in order to produce practical guidance that will assist the newly deployed surgeon in delivering optimal clinical outcomes.